Sulfide-based solid electrolyte having improved moisture stability and ionic conductivity

By introducing sulfur-silver germanium ore-type crystal structure and doping elements with oxidation number 4 and transition metals with oxidation number 6 into sulfide solid electrolytes, the instability problem of sulfide-like solid electrolytes in a moisture environment is solved, and higher ionic conductivity and moisture stability are achieved, the generation of toxic gases is reduced, and the overall performance of the battery is improved.

CN119905647APending Publication Date: 2025-04-29HYUNDAI MOTOR CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410970949.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-26
Filing Date
2024-07-19
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Sulfide solid electrolytes have high moisture reactivity when exposed to the atmosphere, resulting in the production of toxic hydrogen sulfide gas, and their interface stability between the electrode material and the electrolyte is poor, affecting the life and performance of the battery.

Method used

The sulfide-based solid electrolyte with a sulfide-silver germanium ore crystal structure is adopted to improve its ionic conductivity and moisture stability by doping elements with an oxidation number of 4 and a transition metal with an oxidation number of 6, and the generation of toxic hydrogen sulfide gas is inhibited by the reaction between the transition metal and sulfur.

Benefits of technology

It significantly improves the ionic conductivity and moisture stability of sulfide-based solid electrolytes, reduces the generation of toxic hydrogen sulfide gas, enhances the interface stability between the electrode and the electrolyte, and thus improves the performance and life of all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905647A_ABST
    Figure CN119905647A_ABST
Patent Text Reader

Abstract

The sulfide-based solid electrolyte has an argyrodite-type crystal structure doped with an element having an oxidation number of 4 and a transition metal having an oxidation number of 6 in order to improve the moisture stability and ionic conductivity of the sulfide-based solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a sulfide-based solid electrolyte having an argyrodite-type crystal structure. More specifically, it relates to a sulfide-based solid electrolyte having an argyrodite-type crystal structure doped with an element having an oxidation number of 4 and a transition metal having an oxidation number of 6, so as to improve the moisture stability and ion conductivity of the sulfide-based solid electrolyte. Background Art

[0002] Lithium-ion batteries are widely used in various devices that require energy storage. Depending on the application field, they require various battery characteristics such as high energy density, long cycle life, fast charging and discharging, and high and low temperature driving performance.

[0003] Recently, avoiding the use of fossil fuels to solve the problem of carbon dioxide (CO 2 ) has generated great interest in electric vehicles using secondary batteries in the automotive industry. When using currently developed lithium-ion batteries, electric vehicles can travel about 400 kilometers on a single charge, but problems such as instability at high temperatures and fire still exist. To solve these problems, many companies are competing to develop next-generation secondary batteries.

[0004] All-solid-state batteries, which are attracting much attention as next-generation secondary batteries, include all elements formed of solids and have advantages such as low risk of fire and explosion and high mechanical strength compared to lithium-ion batteries that use flammable organic solvents as electrolyte solutions.

[0005] As a solid electrolyte used for an all-solid-state battery, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, or the like can be used, and preferably, a sulfide-based solid electrolyte having high lithium ion conductivity can be used.

[0006] However, sulfide-based solid electrolytes have high water reactivity when exposed to the atmosphere, thus generating toxic hydrogen sulfide (H 2 S) gas, so the stability in the air is poor. In addition, sulfide-based solid electrolytes have unstable interfaces due to the contact between the cathode material or the anode material and the sulfide-based solid electrolyte, so they have low efficiency life characteristics, and the interface resistance between the electrode and the solid electrolyte may not be avoided.

[0007] To address these issues, various studies are underway to improve not only the ionic conductivity of sulfide-based solid electrolytes but also the moisture reactivity and interface stability of all-solid-state batteries.

[0008] The above information disclosed in this background technology section is only for enhancement of understanding of the background of the present disclosure and therefore it may contain information that does not constitute the prior art that is already known in the country to a person of ordinary skill in the art. Summary of the Invention

[0009] The present disclosure is dedicated to solving the above problems related to the prior art, and the object of the present disclosure is to minimize the generation of toxic hydrogen sulfide (H 2 S) gas by suppressing hydrolysis between the sulfide-based solid electrolyte and moisture (H 2 2O).

[0010] Another object of the present disclosure is to improve the interfacial stability between the sulfide-based solid electrolyte and the electrode by increasing the ionic conductivity of the sulfide-based solid electrolyte.

[0011] In one aspect, the present disclosure provides a sulfide-based solid electrolyte represented by the following chemical formula.

[0012] Chemical Formula 1:

[0013] Li 5+2x+y A x Sb y B 1-x-y S 5-z Se z X

[0014] Here, A is an element with an oxidation number of 4, B is a transition metal with an oxidation number of 6, X is at least one selected from Cl, Br, I, and combinations thereof, 0 < x < 1, 0 < y < 1, 0 < x + y < 1, and 0 < z < 5.

[0015] In a preferred embodiment, the element with an oxidation number of 4 may include one selected from silicon (Si), germanium (Ge), tin (Sn), and combinations thereof.

[0016] In another preferred embodiment, the transition metal with an oxidation number of 6 may include one selected from tungsten (W), molybdenum (Mo), and combinations thereof.

[0017] In another preferred embodiment, the sulfide-based solid electrolyte may have a thiogermanate-type crystal structure.

[0018] In another preferred embodiment, the element with an oxidation number of 4 and the transition metal with an oxidation number of 6 may be located at the 4b site of the thiogermanate-type crystal structure.

[0019] In another preferred embodiment, the 1 - x - y configuration indicating the amount of the transition metal with an oxidation number of 6 may be greater than 0 but less than 0.5.

[0020] In another preferred embodiment, z may be greater than 0 but less than 3.5.

[0021] In another further preferred embodiment, the sulfide-based solid electrolyte may belong to the space group F - 43m.

[0022] In another further preferred embodiment, selenium (Se) may replace at least some of the sulfur (S).

[0023] Other aspects and preferred embodiments of the present disclosure are discussed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The above and other features of the present disclosure will now be described in detail with reference to certain exemplary embodiments of the present disclosure shown in the accompanying drawings, which are given hereinafter by way of illustration only and thus do not limit the present disclosure, and in which:

[0025] Figure 1 is a diagram showing the crystal structure of a sulfide-based solid electrolyte according to the present disclosure;

[0026] Figure 2 is a diagram showing the migration path of lithium ions in a sulfide-based solid electrolyte doped with silicon (Si) using molecular dynamics simulation;

[0027] Figure 3 is a diagram showing a migration path of lithium ions in a sulfide-based solid electrolyte doped with silicon (Si) and tungsten (W) using molecular dynamics simulation; and

[0028] Figure 4 is a diagram showing migration paths of lithium ions in a sulfide-based solid electrolyte doped with silicon (Si) and tungsten (W) and doped with selenium (Se) as a substitute for some sulfur (S) using molecular dynamics simulation.

[0029] It should be understood that the accompanying drawings are not necessarily drawn to scale, but rather are simplified representations of various preferred features illustrating the basic principles of the present disclosure to a certain extent. The specific design features of the present disclosure as disclosed herein, including, for example, specific dimensions, orientations, locations and shapes, will be determined in part by specific intended applications and use environments.

[0030] In the drawings, reference numbers refer to the same or equivalent parts of the present disclosure throughout the several figures of the drawing. DETAILED DESCRIPTION

[0031] With reference to the accompanying drawings, the above-mentioned objects, other objects, advantages and features of the present disclosure will become apparent from the description of the embodiments given below. However, the present disclosure is not limited to the embodiments disclosed herein and can be implemented in various different forms. These embodiments are provided to make the description of the present disclosure comprehensive and to fully convey the scope of the present disclosure to those skilled in the art.

[0032] In the accompanying drawings, the same or similar elements are represented by the same reference numerals, even if they are depicted in different drawings. In the accompanying drawings, for clarity of description, the size of the structure may be exaggerated compared to the actual size of the structure. In the following description of the embodiment, terms such as "first" and "second" may be used to describe various elements, but these elements are not limited. These terms are only used to distinguish an element from other elements. For example, without departing from the scope and spirit of the present disclosure, the first element may be named as the second element, and similarly, the second element may be referred to as the first element. Singular expressions may include plural expressions unless they have significantly different contextual meanings.

[0033] In the description of the following embodiments, terms such as "comprises", "includes" and "having" should be interpreted as indicating the presence of the features, numbers, steps, operations, elements or components or combinations thereof described in the description, and do not exclude the presence of one or more other features, numbers, steps, operations, elements, components or combinations thereof, or the possibility of adding features, numbers, steps, operations, elements, components or combinations thereof. In addition, it should be understood that when a component, such as a layer, film, region or plate, is referred to as being "on" another component, the component may be "directly" located "on" the other component, or other components may be between the two components. In the same way, it is understood that when a component, such as a layer, film, region or plate, is referred to as being "under" another component, the component may be "directly" located "under" the other component, or other components may be between the two components.

[0034] All numbers, values ​​and / or expressions representing the amount of components, reaction conditions, polymer compositions and blends used in the description are approximate values, which reflect the various measurement uncertainties that arise when these values ​​are obtained from essentially different things, and therefore should be understood as, unless otherwise stated, they are modified by the term "about". In addition, it should be understood that if a numerical range is disclosed in the specification, the range includes all continuous values ​​from the minimum value to the maximum value of the range unless otherwise stated. In addition, if such a range refers to an integer, the range includes all integers from the minimum integer to the maximum integer unless otherwise stated.

[0035] In the following description of the embodiments, it should be understood that when stating a range of a variable, the variable includes all values ​​within the stated range, including the endpoints of the stated range. For example, it is understood that the range of "5 to 10" includes not only the values ​​of 5, 6, 7, 8, 9 and 10, but also any sub-ranges, such as the sub-range of 6 to 10, the sub-range of 7 to 10, the sub-range of 6 to 9 and the sub-range of 7 to 9, and any values ​​between valid integers within the range, such as 5.5, 6.5, 7.5, 5.5 to 8.5 and 6.5 to 9. In addition, for example, it is understood that the range of "10% to 30%" includes not only all integers including the values ​​of 10%, 11%, 12%, 13%, ... 30%, but also any sub-ranges, such as the sub-range of 10% to 15%, the sub-range of 12% to 18% and the sub-range of 20% to 30%, and any values ​​between valid integers within the range, such as 10.5%, 15.5% and 25.5%.

[0036] Sulfide-based solid electrolytes are being extensively studied around the world because they have high lithium ion conductivity and electrochemical stability. Sulfide-based solid electrolytes are classified into crystalline and amorphous types according to the presence or absence of a crystal structure. As representative examples of the crystalline type, there are sulfo-LiSiCON-type crystal structures, LGPS-type crystal structures, and argyrodite-type crystal structures, and the amorphous type may have a glass structure or a glass-ceramic structure depending on the heat treatment temperature.

[0037] Argentum-type crystal structure is a kind of solid electrolyte, which has the same structure as Ag. 8 G JZ 6 The crystal structure of argyrodite is the same as that of argyrodite and exhibits lithium ion conductivity. + ) A representative example of a Li-argyrodite electrolyte with high conductivity. 7 PS 6 and Li 6 PS 5 X (X is Cl, Br or I).

[0038] Figure 1 is a diagram showing the crystal structure of a sulfide-based solid electrolyte according to the present disclosure. Figure 1 The sulfide-based solid electrolyte shown in can be expressed as the following Chemical Formula 1.

[0039] Chemical formula 1:

[0040] Li 5+2x+y A x Sb y B 1-x-y S 5-z Sez X

[0041] In Chemical Formula 1, A is an element with an oxidation number of 4, B is a transition metal with an oxidation number of 6, and X is at least one selected from Cl, Br, I, and combinations thereof, where 0 < x < 1, 0 < y < 1, 0 < x + y < 1, and 0 < z < 5.

[0042] The sulfide-based solid electrolyte according to the present disclosure may have a thiogermanate crystal structure. Referring to Figure 1 , in the thiogermanate crystal structure, sulfur (S) may form tetrahedrons AS 4 3- and BS 4 3- and SbS 4 3- respectively around elements A and B and antimony (Sb) as the centers. Here, the centers of the tetrahedrons may be located at the 4b sites.

[0043] The conventional sulfide-based solid electrolyte Li 6 PS 5 X (where X is Cl, Br, or I) includes tetrahedron PS 4 3- in the crystal structure, and phosphorus (P) may be located at the center of the tetrahedron. Referring to this, in the present disclosure, the phosphorus (P) sites of the conventional sulfide-based solid electrolyte Li 6 PS 5 X may alternatively be doped with elements A and B and antimony (Sb).

[0044] Here, the sulfide-based solid electrolyte according to the present disclosure may be configured such that elements A and B and antimony (Sb) may replace all of the phosphorus (P) of the conventional sulfide-based solid electrolyte having the composition Li 6 PS 5 X. Therefore, the sulfide-based solid electrolyte according to the present disclosure may not include phosphorus (P).

[0045] In addition, referring to Figure 1 , elements A and B and antimony (Sb) may be represented as being located at the 4b sites of the thiogermanate crystal structure.

[0046] According to the present disclosure, when the transition metal B with an oxidation number of 6 and a large ionic radius replaces the site of phosphorus (P), the lattice volume may increase. With the increase in the lattice volume, the activation energy for the migration of lithium ions in the lattice may be reduced, thereby increasing the lithium ion conductivity.

[0047] In addition, the transition metal B that replaces the phosphorus (P) site can cause the appearance of vacancies in the lattice. The appearance of vacancies can promote the formation of a cubic phase, and the cubic phase has sufficient lithium ions (Li + ) migration path, thus promoting 3D fast conduction. As a result, the lithium ion conductivity of the sulfide solid electrolyte can be improved.

[0048] Here, 1-xy indicating the amount of transition metal B in the sulfide-based solid electrolyte may be greater than 0 but less than 1. Preferably, 1-xy may be greater than 0 but less than 0.5. When 1-xy indicating the amount of transition metal B in the sulfide-based solid electrolyte is less than 0.5, the lithium ion conductivity of the sulfide-based solid electrolyte may be further improved.

[0049] In addition, the moisture (H 2 O) reacts with the sulfide solid electrolyte to produce H 2 During the process of S gas, transition metal B reacts with sulfur (S) to form BS 2 , thereby suppressing the generation of toxic hydrogen sulfide gas.

[0050] In one embodiment, the element A having an oxidation number of 4 may include a Group 4 element on the periodic table. Preferably, the element A may include at least one selected from silicon (Si), germanium (Ge), tin (Sn), and combinations thereof. In addition, the transition metal B having an oxidation number of 6 may include at least one selected from tungsten (W), molybdenum (Mo), and combinations thereof.

[0051] z indicating the amount of selenium (Se) in the sulfide-based solid electrolyte may be greater than 0 but less than 5. Preferably, z may be greater than 0 but less than 3.5. When z indicating the amount of selenium (Se) in the sulfide-based solid electrolyte is less than 3.5, H generation caused by hydrolysis may be further suppressed. 2 Generation of S gas. Here, selenium (Se) may replace at least some of sulfur (S).

[0052] In addition, the sulfide-based solid electrolyte according to the present disclosure may belong to, for example, a cubic crystal system, and more specifically, may belong to space group F-43m.

[0053] Hereinafter, the present disclosure will be described in more detail through the following examples and comparative examples. The following examples and comparative examples are only used to exemplarily describe the present disclosure and are not intended to limit the scope and spirit of the present disclosure.

[0054] Test Example 1: Lithium Ion (Li + ) Detection of migration paths

[0055] Molecular dynamics simulations were used to predict the +) in sulfide solid electrolytes with an argyrodite-type crystal structure.

[0056] Specifically, for a composition of Li excluding a transition metal having an oxidation number of 6 and selenium (Se), 6.5 Si 0.5 Sb 0.5 S 5 I's sulfide solid electrolyte was subjected to molecular dynamics simulation. The simulation results are shown in Figure 2 Here, the green area indicates the tetrahedron including Si and Sb, and the purple line indicates the lithium ion (Li + ) migration path.

[0057] In addition, for a composition not including selenium (Se), Li 6.25 Si 0.5 Sb 0.25 W 0.25 S 5 I's sulfide solid electrolyte was subjected to molecular dynamics simulation. The simulation results are shown in Figure 3 Here, the blue area indicates the tetrahedron including Si, Sb, W and S, and the purple line indicates the lithium ion (Li + ) migration path.

[0058] In addition, for a composition including a transition metal having an oxidation number of 6 and selenium (Se) but not including antimony (Sb), Li 6.5 Si 0.75 W 0.25 S 4.75 Se 0.25 The molecular dynamics simulation of the sulfide solid electrolyte of I was carried out, and the simulation results are shown in Figure 4 Here, the blue area indicates the tetrahedron including Si, W, Se and S, and the purple line indicates the lithium ion (Li + ) migration path.

[0059] Reference Figure 2-4 It can be confirmed that in a sulfide-based solid electrolyte including W as a transition metal with an oxidation number of 6, lithium ions (Li + ) migrates more actively around the tetrahedron. Therefore, it can be predicted that the sulfide-based solid electrolyte including W has higher lithium ion conductivity.

[0060] Experimental Example 2: Lithium ion conductivity and synthesis possibility of sulfide-based solid electrolytes with various compositions

[0061] The lithium ion conductivity and activation energy (E) required for lithium ion migration of sulfide-based solid electrolytes with various compositions were calculated using molecular dynamics calculation methods and machine learning. a ) and the energy above hull (Ehull ), as shown in Table 1 below.

[0062] Shell energy (E hull ) is an indicator for evaluating the synthetic feasibility of a material. It is determined that the shell energy (E hull ) is closer to 0, the higher the synthetic probability of the material, and is usually evaluated as the energy on the shell (E hull ) is 100 hours or less, the material can be synthesized.

[0063] The 80% ionic conductivity (80% IC) was calculated by the following equation.

[0064] equation:

[0065]

[0066] Here, X c Indicates the crystallinity, in the case of 80% crystalline structure, 0.8 is substituted. calc. Indicates the calculated lithium ion conductivity, namely bulk ionic conductivity (BIC).

[0067] Table 1

[0068]

[0069]

[0070] Generally, it is determined that when the 80% ion conductivity of the solid electrolyte is 1 mS / cm or more, there is a possibility of commercialization of the solid electrolyte. Referring to Table 1, it is calculated that the bulk ion conductivity of the sulfide-based solid electrolyte having phosphorus (P) is low.

[0071] Experimental Example 3: Hydrolysis reaction of sulfide-based solid electrolytes with various compositions and hydrogen sulfide gas generation performance

[0072] In order to evaluate the moisture stability of the sulfide-based solid electrolyte according to the present disclosure, the hydrogen sulfide gas generation energy of the sulfide-based solid electrolyte was calculated using density functional theory (DFT). The calculation process is as follows.

[0073] 1). Designed the solid electrolyte SE and H to be calculated 2 The pseudo-binary reaction formula of the product composition C is formed as a result of the reaction between O.

[0074] Reaction 1: C 产物 (SE, H 2 O, x) = x·C(SE) + (1-x)C(H 2 O)

[0075] 2). The reaction energy of such a formula can be calculated as follows.

[0076] Reaction 2: E 反应 (SE, H 2 O, x) = Eeq(C 产物 (SE, H 2 O,x))-E(C 产物 (SE, H 2 O,x))

[0077] Here, eq indicates the phase equilibrium state between the products obtained from the reaction formula (1).

[0078] 3) Calculate the reaction energy E of x by substituting the value of x in the range of 0<x<1 into the above formula 反应 , and the reaction with the x value having the lowest reaction energy is determined as the solid electrolyte SE to be calculated with H 2 The reaction between O.

[0079] 4). Relative reaction equation to H 2 S is normalized to compare the reaction energies of various solid electrolyte SEs.

[0080] 5). The hydrogen sulfide gas generation energy Eg is finally obtained by dividing the reaction energy by the conversion factor obtained by taking into account the conversion rate indicating that sulfur (S) contained in the solid electrolyte SE as a reactant participates in the generation of hydrogen sulfide gas.

[0081] The hydrogen sulfide gas generation energy Eg of the solid electrolyte SE and the reaction formula for calculating the hydrogen sulfide gas generation energy Eg are listed in Table 2 below.

[0082] Table 2

[0083]

[0084]

[0085]

[0086]

[0087]

[0088] As the gas generation energy decreases, hydrogen sulfide gas is more easily generated in the hydrolysis of the sulfide-based solid electrolyte. That is, as the gas generation energy increases, the generation of hydrogen sulfide gas can be suppressed and the moisture stability can be improved.

[0089] Referring to Table 2, it is calculated that the gas generation energy of the sulfide solid electrolyte doped with an element with an oxidation number of 4 or a transition metal with an oxidation number of 6 is higher. It is predicted that tungsten (W) and molybdenum (Mo) react with sulfur (S) to form WS2 and MoS 2 , thus suppressing the generation of H 2 S gas.

[0090] Experimental Example 4: Interface energy between sulfide solid electrolytes with various compositions and various elements of the cathode

[0091] Calculate the interfacial reaction energy between the cathode active material, the coating composition that is usually included in the cathode, and sulfide-based solid electrolytes with various compositions through computer simulation. The detailed calculation method is as follows.

[0092] Equation eq1: xC a +(1 - x)C b →C equil

[0093] (C a and C b = the compositions of the two contacting phases, C equil = the lower phase equilibrium energy, and 0 < x < 1) Equation eq2: ΔE[C a , C b = min{E pd [xC a +(1 - x)C b - xE[C a -(1 - x)E[C b}

[0094] (E pd : the combination of reaction products with the lowest energy in xC a +(1 - x)C b ))

[0095] The relevant energies calculated using DFT can be obtained from the database of the Materials Project, and there is a function to find the minimum value in the Materials Project.

[0096] To describe the phenomena in the battery cell, Equation eq3 is derived using Equation eq2.

[0097] Equation eq3: φ pd [c, μ Li = min[E pd [c + μ Li - n Li [c]μ Li}

[0098] φ pd [c, μ Li indicates the composition c with the lowest energy in μ Li in the same way as E pd . Here, the lithium potential determined according to the calculated average cathode voltage is used.

[0099] In equation eq4, by allowing the electrolyte to equilibrate with the external lithium potential and react with the cathode, the potential at the interface changes, and the interface stability is given by μ Li The size of Δφ determines the thermodynamic stability.

[0100] Equation eq4:

[0101]

[0102] Finally, the interfacial reaction energy between the electrolyte and the cathode can be confirmed using Δφ.

[0103] The interfacial reaction energies of sulfide-based solid electrolytes with various compositions were calculated using the above method, as shown in Table 3 below.

[0104] Table 3

[0105]

[0106]

[0107] Referring to Table 3, it can be confirmed that the interfacial reaction energy of the sulfide-based solid electrolyte according to the present disclosure is higher than that of the conventional argyrodite-type sulfide-based solid electrolyte (Li 6 PS 5 Cl). Thus, it can be predicted that a decomposition reaction is difficult to cause in the sulfide-based solid electrolyte according to the present disclosure, and therefore, the stability at the interface of the sulfide-based solid electrolyte according to the present disclosure can be improved.

[0108] As is apparent from the above description, the present disclosure provides a sulfide-based solid electrolyte having an argyrodite-type crystal structure including an element having an oxidation number of 4 and a transition metal having an oxidation number of 6, thereby improving the ionic conductivity and moisture stability of the sulfide-based solid electrolyte in a balanced manner.

[0109] The present disclosure has been described in detail with reference to the preferred embodiments of the present disclosure. However, it will be appreciated by those skilled in the art that changes may be made in these embodiments without departing from the principles and spirit of the present disclosure, the scope of which is defined in the claims and their equivalents.

Claims

1. A sulfide solid electrolyte, represented by Li 5+2x+y A x Sb y B 1-x-y S 5-z Se z X; in, A is an element with an oxidation number of 4, B is a transition metal with an oxidation number of 6, X is at least one selected from Cl, Br, I, and combinations thereof, 0 < x < 1, 0 < y < 1, 0 < x + y < 1, and 0 < z < 5.

2. The sulfide-based solid electrolyte according to claim 1, wherein the element with an oxidation number of 4 includes one selected from silicon Si, germanium Ge, tin Sn, and combinations thereof.

3. The sulfide-based solid electrolyte according to claim 1, wherein the transition metal with an oxidation number of 6 includes one selected from tungsten W, molybdenum Mo, and combinations thereof.

4. The sulfide-based solid electrolyte according to claim 1, which is configured to have a thioargentite crystal structure.

5. The sulfide-based solid electrolyte according to claim 4, wherein the element with an oxidation number of 4 and the transition metal with an oxidation number of 6 are located at the 4b sites of the thioargentite crystal structure.

6. The sulfide-based solid electrolyte according to claim 1, wherein 1 - x - y is configured to indicate that the amount of the transition metal with an oxidation number of 6 is greater than 0 but less than 0.

5.

7. The sulfide-based solid electrolyte according to claim 1, wherein z is greater than 0 but less than 3.

5.

8. The sulfide-based solid electrolyte according to claim 1, which is configured to belong to the space group F-43m.

9. The sulfide-based solid electrolyte according to claim 1, wherein selenium Se replaces at least some of sulfur S.